Regulation of the Larval Transcriptome of Diatraea saccharalis (Lepidoptera: Crambidae) by Maternal and Other Factors of the Parasitoid Cotesia flavipes (Hymenoptera: Braconidae) - Merlin, Bruna Laís; Cônsoli, Fernando Luis (Frontiers in Physiology, 2019)
Koinobiont endoparasitoid wasps regulate the host’s physiology to their own benefit during their growth and development, using maternal, immature and/or derived-tissue weaponry. The tools used to subdue the wasps’ hosts interfere directly with host transcription activity. The broad range of host tissues and pathways affected impedes our overall understanding of the host-regulation process during parasitoid development. Next-generation sequencing and de novo transcriptomes are helpful approaches to broad questions, including in non-model organisms. In the present study, we used Illumina sequencing to assemble a de novo reference transcriptome of the sugarcane borer Diatraea saccharalis, to investigate the regulation of host gene expression by the larval endoparasitoid Cotesia flavipes. We obtained 174,809,358 reads and assembled 144,116 transcripts, of which 44,325 were putatively identified as lepidopteran genes and represented a substantial number of pathways that are well described in other lepidopteran species. Comparative transcriptome analyses of unparasitized versus parasitized larvae identified 1,432 transcripts of D. saccharalis that were up-regulated under parasitization by C. flavipes, while 1,027 transcripts were down-regulated. Comparison of the transcriptomes of unparasitized and pseudoparasitized D. saccharalis larvae led to the identification of 1,253 up-regulated transcripts and 972 down-regulated transcripts in the pseudoparasitized larvae. Analysis of the differentially expressed transcripts showed that C. flavipes regulated several pathways, including the Ca+2 transduction signaling pathway, glycolysis/gluconeogenesis, chitin metabolism, and hormone biosynthesis and degradation, as well as the immune system, allowing us to identify key target genes involved in the metabolism and development of D. saccharalis.